2015
DOI: 10.1186/s12916-015-0331-6
|View full text |Cite
|
Sign up to set email alerts
|

Hair regrowth in alopecia areata patients following Stem Cell Educator therapy

Abstract: BackgroundAlopecia areata (AA) is one of the most common autoimmune diseases and targets the hair follicles, with high impact on the quality of life and self-esteem of patients due to hair loss. Clinical management and outcomes are challenged by current limited immunosuppressive and immunomodulating regimens.MethodsWe have developed a Stem Cell Educator therapy in which a patient’s blood is circulated through a closed-loop system that separates mononuclear cells from the whole blood, allows the cells to briefl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 51 publications
0
59
0
3
Order By: Relevance
“…Stem cell educator therapy has shown some initial success 203 . This approach uses a closed-loop system to isolate mononuclear cells derived from patients with alopecia areata, allows them to interact with human cord blood-derived multipotent stem cells, and then returns the “educated” cells into the patient’s circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell educator therapy has shown some initial success 203 . This approach uses a closed-loop system to isolate mononuclear cells derived from patients with alopecia areata, allows them to interact with human cord blood-derived multipotent stem cells, and then returns the “educated” cells into the patient’s circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, AA frequently remits spontaneously, presumably as a result of reestablishment of HF IP [1]. One major challenge of future AA therapy should be, then, to accelerate and promote this process (for detailed review, see [1,4,5,13,43,44]) (Fig. 2).…”
Section: Aa Disease Immunopathogenesismentioning
confidence: 99%
“…After injection of the cultured bulge and DP cells into deep dermis, epidermis forming ability of the cells was assessed. The authors suggested their methodology as a relevant source of bioengineered hair follicles for hair transplantation therapies in alopecia [120].…”
Section: Preliminary Hair Follicle Generation Studies and Obstacles Imentioning
confidence: 99%